Verbal Sign in Music Video of This Is America by Childish Gambino - Saraswathy, Ida Ayu Tantri; Beratha, Ni Luh Sutjiati; Rajeg, I Made (Humanis, 2022)
This study is aimed to identify the verbal sign used in the music video “This is America” by Childish Gambino. This study used a qualitative library research approach. Based on that approach, the data were described according to the theories applied in this study. The data collected by note taking and documentation methods. The first theory applied in this study was the verbal sign proposed by Dyer. It was used to analyze the verbal sign in the music video. The second theory applied was the theory of meaning proposed by Leech to analyze the meaning used in the music video. The results showed that the meaning of the lyrics refers to the African American society’s problem of racism, police brutality, violence and gun possession. The lyrics contained the connotative and conceptual meaning.